Comportamento de garanhões durante a coleta de sêmen pré e pós-suplementação com compostos naturais e antioxidante - (:unkn) unknown (Universidade Brasil, 2022)
The stallion performance and semen processing out of the breeding season period is essential for optimizing reproductive service and management. The study described the reproductive behavior of stallions during semen collection pre and post-supplementation with natural compounds and antioxidants. Four adult Quarter Horse stallions weighing between 416 and 505 kg and active sexual maturity (6 to 24 years) were used during the routine of semen collection in a breeding center. The experiment performed in a commercial stud farm, located in the city of Araraquara, SP. The pre and post-supplementation period consisted of eight successive semen collections, with an interval of 48 hours. Between the initial and final period (75 days), the animals received 6 kg/day of commercial pelleted feed, with supplementation (45 g of the product/day) based on L-carnitine (334g/kg), beta carotene (44, 5 g/kg), folic acid (1200 mg/kg), vitamin C (22.3 g/kg) and vitamin E (27800 IU/kg), water and mineral salt ad libitum. The behavioral repertoire (interval and number) was registered by evaluating the videos recorded during the collection, considering variables since hygiene management, mounting, semen collection and completion of the procedure. The study used an “Quasi- Experimental Design” and stallion behavior pre and post supplementation was compared. The behavior repertoire data was evaluated by comparing treatment in different moments and the variable means were submitted to non-parametric Kruskal-Wallis test, at the level of 5% (P<0.05) of probability. The individual responses of each stallion revealed changes in the post-supplementation period considering the behavior repertory during semen collection, which are related to reproductive performance and they could be influenced by conditioning and supplementation.
Keywords: Equino; Etologia; Nutracêutico; Performance; Reprodução; Produção Animal